The Influence of Profitability, Leverage and Firm Size on Company Decisions to Practice Transfer Pricing - Fazriah, Tami Luthfiani; Alvina, Siti Nurul; Nuryaman (CENTRAL ASIA AND THE CAUCASUS, 2022)
The research is based on the fact that there are still many cases of transfer pricing practices in various companies. The aim is to test whether the effect of transfer pricing is influenced by profitability, leverage and firm size. This type of research is quantitative using the explanatory method. The sampling technique used purposive sampling with a total sample of 41 companies. This type of research includes quantitative data analysis. Data analysis uses panel data regression. The results show that there is a positive effect of profitability and leverage on transfer pricing, while there is a negative effect of firm size on transfer pricing.